Exposure visit of Government officials to witness the revitalization of traditional water-harvesting haveli systems at the Bhadokhar Haveli in the Tahrauli cluster - Singh, Ramesh; Anantha K.H.; Garg, Kaushal K.; Venkataradha A.; Shukla, Ashok; Reddy, Nagarjuna N. (International Crops Research Institute for the Semi-Arid Tropics, 2025)
This report documents the strategic exposure visit of high-level government delegations, including senior leadership from the Department of Land Resources (DoLR), Government of India, and CEOs of State Level Nodal Agencies (SLNAs) from six states, to the Tahrauli cluster in Uttar Pradesh during October 2025. The visit aimed to demonstrate the efficacy of the Bundelkhand Model - a science-led approach to landscape rejuvenation featuring the revitalization of traditional Haveli water-harvesting systems. Delegates observed firsthand the technical rigor and community-driven mechanisms that have successfully restored groundwater levels and agricultural productivity in this hard-rock region. The visit highlighted the project's scalability, paving the way for potential policy integration into PMKSY WDC 3.0 guidelines and sparking cross-state collaboration to replicate these climate-resilient interventions across India’s drylands.